Transcriptome Analysis of the Melon-Fusarium oxysporum f. sp. melonis Race 1.2 Pathosystem in Susceptible and Resistant Plants - Silvia Sebastiani, M.; Bagnaresi, Paolo; Sestili, Sara; Biselli, Chiara; Zechini, Antonella; Orrù, Luigi; Cattivelli, Luigi; Ficcadenti, Nadia (Frontiers in Plant Science, 2017)
Fusarium oxysporum f. sp. melonis Snyd. & Hans race 1.2 (FOM1.2) is the most virulent and yield-limiting pathogen of melon (Cucumis melo L.) worldwide. Current information suggest that the resistance to race 1.2 is controlled by multiple recessive genes and strongly affected by the environment. RNA-Seq analysis was used to identify candidate resistance genes and to dissect the early molecular processes deployed during melon-FOM1.2 interaction in the resistant doubled haploid line NAD and in the susceptible genotype Charentais-T (CHT) at 24 and 48 hours post inoculation (hpi). The transcriptome analysis of the NAD-FOM1.2 interaction identified 2,461 and 821 differentially expressed genes (DEGs) at 24 hpi and at 48 hpi, respectively, while in susceptible combination CHT-FOM1.2, 882 and 2,237 DEGs were recovered at 24 hpi and at 48 hpi, respectively. The overall expression profile suggests a prompt activation of the defence responses in NAD due to its basal defence-related machinery that allows an early pathogen recognition. Gene Ontology (GO) enrichment analyses revealed a total of 57 GO terms shared by both genotypes and consistent with response to fungal infection. GO classes named "chitinase activity", "cellulase activity", "defence response, incompatible interaction", "auxin polar transport" emerged as major factors of resistance to FOM1.2. The data indicated that NAD reacts to FOM1.2 with a fine regulation of Ca2+-mediated signalling pathways, cell wall reorganization and hormone crosstalk (jasmonate and ethylene, auxin and abscissic acid). Several unannotated transcripts were recovered providing a basis for a further exploration of the melon resistance genes. DEGs belonging to the FOM1.2 genome were also detected in planta as a resource for the identification of potential pathogenicity factors. This work provides a broader view of the dynamic changes of the melon transcriptome triggered by FOM1.2 and highlights that the resistance response of NAD is mainly signalled by jasmonic acid and ethylene pathways mediated by ABA and auxin. The role of candidate plant and fungal responsive genes involved in the resistance is discussed.